Aspects of Marwānid political thought: between religious and tribal modes of legitimation - Haidar, Abdulla Hassan (The University of Edinburgh, 2025)
The aim of this thesis is to study some aspects of Marwānid political thought by looking at poetry and epistles produced in the Marwānid era. This thesis is built on the many contributions in the field of Islamic studies and history that addressed the question of the Marwānid language of legitimacy. However, there are two shortcomings in those studies. First, earlier strands of scholarship downplayed the religious profile of the Marwānids, which should have paved the way for studying other modes of legitimation, including tribal. However, examining this mode was mainly neglected and remains a gap that needs to be addressed in the field. Even when the academic view on the religious profile of the Marwānid changed, starting in the eighties, most of the modern contributions on the issue focus on aspects of the religious mode of legitimation without giving attention to the tribal idioms that the Marwānid propagandists used. Second, while poetry has always been used to study aspects of Marwānid history, these employments of poetry were not systematic. The thesis aims to amend this and suggests that poetry produced in the Marwānid era is likely a reliable and particularly rich source that needs to be taken into consideration when studying Marwānid history. It shows that poetry can provide us with a better understanding of the history of Marwānid political thought than any other source. The thesis further focuses on the interplay between the two prominent modes of legitimation, religious and tribal, used by the propagandists of the Marwānid dynasty. It looks at how these two prominent modes were used to articulate the Marwānid language of legitimacy. The thesis shows that their propagandists created a complex language of legitimacy. Throughout the Marwānid history, the tribal idioms were equally important as the religious idioms. This indicates that we need to look at all legitimisation modes used by their propagandists to understand the complexity of their political programme.
Keywords: Marwānid; Political thought; Legitimation; Religious mode; Tribal mode